HARGA SAHAM SYARIAH SELAMA MASA COVID-19 - Rahmah, Nabila; Daud, Rulfah M. (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to identify and analyze the influencing factors of Islamic stock prices during COVID-19 of companies listed on the Jakarta Islamic Index. The population in this study are all companies listed on the Jakarta Islamic Index for 2019-2021. The samples were selected by a saturated sampling technique, resulting in 90 companies as samples. The research is quantitative with secondary data. Data analysis used panel data regression analysis with the help of the EViews 9 data processing application. The results of this study show that the current ratio and debt-to-equity ratio partially affect Sharia stock prices, whereas the return on equity, inflation, and gross domestic product does not affect Sharia stock prices. Simultaneously, the current ratio, return on equity, debt-to-equity ratio, inflation, and gross domestic product affect Sharia stock prices.